ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN DALAM PEMBELAJARAN REALISTIK BERBASIS MASALAH - Azizah, Siti Nur (MAXIMA : Jurnal Pendidikan Matematika, 2024)
One of the main problems in classroom learning. Solving mathematical problems is still low. The purpose of this study is to explain the potential problems of problem-based teaching mats. Necessity. The research method used is quantitative descriptive. In the 21st Century, education activists are required to present teaching materials that can be used independently and are easy for students to access. This research aims to obtain information about learning media, learning methods, and students' mathematical literacy skills. The quantitative descriptive analysis used in this study was carried out by way of a survey and using several literature studies. The results of this study found that students still have difficulty in associating their abilities with many problems that exist in mathematics, social problems, and applying mathematical concepts. The media and learning methods that have been used have not been able to stimulate students' mathematical literacy.